UPLC-QTOF/MSE and Bioassay Are Available Approaches for Identifying Quality Fluctuation of Xueshuantong Lyophilized Powder in Clinic - Yang, Zhi-Rui; Wang, Zi-Hao; Tang, Jin-Fa; Yan, Yan; Yue, Shi-Jun; Feng, Wu-Wen; Shi, Zheng-Yuan; Meng, Xin-Tong; Peng, Cheng; Wang, Chang-Yun; Meng, Da-Li; Yan, Dan (Frontiers in Pharmacology, 2018)
Xueshuantong Lyophilized Powder (XST), consisting of a series of saponins extracted from Panax notoginseng, is widely applied to treat acute cerebral infarction, stroke and coronary heart disease in China. However, most adverse drug reactions (ADR) in clinic are caused by quality problems of XST. In this study, 6 batches of certainly abnormal, 4 batches of possibly abnormal XST and 8 batches of normal XST were obtained from the clinical practice. Their quality fluctuations were identified by ultra-performance liquid chromatography coupled with an electrospray ionization quadrupole time-of-flight mass spectrometry operating in MSE mode (UPLC-QTOF/MSE) and bioassays including antithrombin and proplasmin assay. Fourteen potential components responsible for clinical ADR were identified by UPLC-QTOF/MSE, especially ginsenoside Rg1, Rg3, Rb1 and notoginsenoside R1. In addition, 83.3% (5/6) and 50.0% (3/6) certainly abnormal samples could be identified by UPLC-QTOF/MSE and bioassay, respectively. Interestingly, further integration of the two methods could entirely identify all the certainly abnormal samples and inferred that all the possibly abnormal samples were closely related to their quality fluctuation. It indicates that it is advisable to combine UPLC-QTOF/MSE and bioassay for identifying quality fluctuation of XST, and thus reduce its ADR in clinic.